Fructose-Induced Insulin Resistance: Prospective Biochemical Mechanisms - Tamimi, Lina Nasser; Ahmad, Mousa Numan; Qinna, Nidal Adel (Jordan Journal of Agricultural Sciences, 2021)
Increased intake of dietary fructose is markedly associated with multiple negative health outcomes and burdens. Insulin resistance (IR) and type 2 diabetes mellitus (T2DM) are the most common complications that present with conjugated cellular-biochemical abnormalities. This article explains the involvement of increased dietary fructose intake in the occurrence of IR and T2DM and addresses basic metabolic mechanisms. PubMed, Medline, Science Direct, ADI, and WHO databases were searched through June 2021. Current research predicts that over 350 million people may have diabetes by 2030. IR acts as an influencer promoter of T2DM development. IR can occur as a result of high fructose intake. Fructose metabolism results in de novo lipogenesis, while its decreasing effect of peroxisome proliferator-activated receptor (PPAR) activity elevates the levels of inflammatory cytokines, resulting in down-regulation of insulin receptor substrate-1 phosphorylation. Fructose stimulates oxidative stress by activating nicotinamide adenine dinucleotide phosphate oxidase and synthesis of advanced glycation end-products. Fructose also stimulates purine-induced uric acid synthesis and leptin resistance, which contributes to abnormal insulin action. It is crucial to understand the mechanisms of fructose-induced IR via induction of oxidative stress, inflammation, leptin resistance, and uric acid production. This helps prevent and control variable diseases, T2DM being the most.